Changes in litter during the initial leaching phase: an experiment on the leaf litter of Mediterranean species (Soil biology and biochemistry, 1995)
A laboratory experiment was carried out with the litter of 7 Mediterranean species of plants to compare their mass losses during the initial leaching phase of decomposition. To this end, the leaf and needle litter of deciduous, marcescent (deciduous species in which the withered leaves remain on the tree. for several months) and evergreen broad-leaved species and pine was immersed for 10 days in demineralized water, in the dark at 22°C. Samples were taken at 1,6, 24,72, 168 and 240 h. Depending on the species, the litter lost between ‘T-15% of initial dry mass, and water content values were between 130-360% of dry mass. The water absorption rate was positively correlated with the initial cellulose content of the litter and negatively correlated wil:h the initial leaf density, but the water content at the end of the experiment, the leaching rate and the total mass loss were uncorrelated with any of the initial litter characteristics studied. For 100 g of litter at the start (as dry matter), the losses after 240 h of immersion in water were, when they were significant, 5-8 g of C, 70-l 30 mg of N (significant for 3 species), 4-40 mg of soluble sugars and 3 g of inorganic elements (significant for only 2 species). In contrast, the quantities of lignin and cellulose in the litter remained unchanged. Most of the leaching losses (SCrSO%) therefore consisted of C. During leaching, the litter showed a tendency to become more concentrated in cellulose and lignin and poorer in sugars. Pine needle litter was distinguished by its low water absorption and low mass loss during leaching. In general, the litters of deciduous species were more absorbent than the litters of evergreen species. In contrast, the losses of water-soluble substances were not significantly different between these 2 groups of litters. In the broad-leaved species, the losses of water-soluble substances were slower and 2-3 times lower, compared to results already published for species from mesic biomes